ANALISIS PENGARUH TINGKAT INFLASI, NILAI KURS, SUKU BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PADA MASA STIMULUS AMERIKA SERIKAT QUANTITATIFE EASING (QE) TAHUN 2008-2014 - ROKHIM, MUKHAMMAD (Jurnal Akuntansi AKUNESA, 2016)
The global economic crisis hit Indonesia in 2008 with huge impacts on numerous sectors, from macroeconomic variables, they are inflation and exchange rate. Economic crisis could cause a country huge impact that affected everyone, from the country itself or any related countries that had relationships and interests. It can be seen on Indonesian market, Composite Index. In the period of cessation of Quantitative Easing (QE) there is an indication of its impact on the capital market in Indonesia. From the phenomenon above, the author wanted to study the impact of QE on macroeconomic variables in Indonesia, namely inflation rate, exchange rate, and interest rate.Years of research selected from 2008 to 2014, the year in which the US stimulus policy was used. Quantitative Easing is divided into three stages, namely QE I, QE II, QE III. The data were obtained from BI reports which can be accessed on the official BI site, while IHSG data were obtained from stock prices on Yahoofinance. The result of this study implied that all three macroeconomic indicators didn’t have any effect on Composite index. The result was caused by the study period between 2008 – 2014 informed few effects of those three variables on the Composite Index.